Management Influence School Operational Assistance Fund (BOS) on Learning Effectiveness (Case Study Private Madrasah Aliyah in Bandung Regency) - Ade Mahmudin (GoResearch - Research & Publishing House, 2022)
There are new regulations regarding the distribution of School Operational Assistance (BOS) funds and it is often found that new students are accepted in a larger number than the available budget allocation for School Operational Assistance (BOS). This causes the BOS budget to be considered insufficient. Apart from that, because the sources of funds provided by the government are limited for each region, the school has a little difficulty managing the funds that have been provided which can cause the learning process in schools to be less effective. Then, in this study the approach used was a quantitative approach and used data analysis techniques to test the instrument (validity & reliability), partial indicator analysis test, prerequisite test (normality & linearity), and hypothesis testing (simple linear regression analysis, t-test, and coefficient analysis). determination). The result of the research is that there is a significant influence between the management of school operational assistance funds on the effectiveness of learning in private Madrasah Aliyah in Bandung district. And based on the test of the coefficient of determination the value obtained is 32.6% while the rest is influenced by other factors.